(untitled) (TAMADDUN NURI JURNALI, 2025)
This scientific article attempts to scientifically analyze the possibility of solving the following pedagogical tasks by organizing classroom and extracurricular activities to effectively use students’ free time, instilling in them love for our national values, introducing students to "badash" melodies, which are considered our intangible cultural heritage, and the leadership role of the student in the educational process.